2006
DOI: 10.1021/jp061301j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of 2-Nitrophenyl Octyl Ether and Nitrobenzene

Abstract: The pure organic liquids nitrobenzene (NB) and 2-nitrophenyl octyl ether (NPOE) have been studied by means of molecular dynamics simulations. Both solvents are extremely important in various interfacial processes, mainly connected with ion transfer taking place across the interface with water. Thermodynamic (mass density, enthalpy of vaporization, isothermal compressibility, dipole moment) and dynamic (viscosities and self-diffusion coefficients) properties of both liquids have been calculated and are in very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 40 publications
(90 reference statements)
8
48
1
Order By: Relevance
“…The first major difference is the higher density reached in the bulk phase by NB. The bulk density values of both organic liquids agree well with independent calculations from pure-component simulations 7 . The other main difference is that the density oscillations persist for longer distances in the case of NPOE, relative to NB.…”
Section: Figuresupporting
confidence: 79%
See 2 more Smart Citations
“…The first major difference is the higher density reached in the bulk phase by NB. The bulk density values of both organic liquids agree well with independent calculations from pure-component simulations 7 . The other main difference is that the density oscillations persist for longer distances in the case of NPOE, relative to NB.…”
Section: Figuresupporting
confidence: 79%
“…We have concentrated on the orientation of the nitro group because this group is the one involved in hydrogen bonds with water 8 . Furthermore, even though the full nitrobenzene orientation cannot strictly be defined by only two angles, the orientation of the nitro group provides a good estimate of the orientation of the entire NB molecule, since it is preferentially aligned with the aromatic plane 7 . Unfortunately, this is not the case for NPOE, since the orientation of this molecule possesses many more degrees of freedom.…”
Section: Molecular Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…Shao and Pereira et al [78] reported, for first time, the polarization of a nano-interface between water and n-octanol by using a modified version of the classical four electrode voltammetry at ITIES. Additionaly, nitrophenyloctyl ether (NPOE) emerged as a viable non-toxic organic solvent in experiments at the polarized liquid-liquid interface [5,9,37,44,46,[79][80][81][82]. NPOE has a moderate dielectric constant and a high viscosity that makes it a good ionic solvent suitable for kinetic studies.…”
Section: Organic Solvents Used In Biomimetic Membranesmentioning
confidence: 99%
“…Due to the importance of these solvents in chemistry, there is no question that computer simulations of these systems will be of great help for a proper understanding of their solvation features. We have recently presented a comprehensive molecular dynamics study of pure NB and NPOE, including the calculation of thermodynamic, structural and dynamic properties of the bulk liquids, as well as the solvation of potassium and chloride ions [16]. However, a crucial aspect that is missing is a detailed study of the interactions of these solvents with water.…”
Section: Introductionmentioning
confidence: 99%